2008
DOI: 10.1039/b805117h
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in nanoporous solids due to fluid adsorption: thermodynamic analysis and Monte Carlo simulations

Abstract: A thermodynamic analysis based on the osmotic ensemble scheme enables the prediction of structural changes occurring in silicalite-1 zeolite upon halocarbon molecule adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
70
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 31 publications
0
70
0
Order By: Relevance
“…More recent experimental work on the deformation of carbons during the adsorption of different gases has been reported by Fomkin and co-workers [6][7][8] and a dilatometric investigation of the deformation of carbon xerogels has been made by Balzer and co-workers [9] who concluded that micropores in the adsorbents made the most significant contribution to the expansion and contraction of these materials. Recognizing the significance of the effect of adsorption-induced deformation, more attention is paid on this phenomenon for various systems beside carbonaceous materials, such as porous glass [10], zeolites [11], silica gels [12], porous silicon [13,14] and metal-organic frameworks (MOFs) [15,16]. A review of the general area of adsorption deformation has been published by Tvardovski [17].…”
Section: Introductionmentioning
confidence: 99%
“…More recent experimental work on the deformation of carbons during the adsorption of different gases has been reported by Fomkin and co-workers [6][7][8] and a dilatometric investigation of the deformation of carbon xerogels has been made by Balzer and co-workers [9] who concluded that micropores in the adsorbents made the most significant contribution to the expansion and contraction of these materials. Recognizing the significance of the effect of adsorption-induced deformation, more attention is paid on this phenomenon for various systems beside carbonaceous materials, such as porous glass [10], zeolites [11], silica gels [12], porous silicon [13,14] and metal-organic frameworks (MOFs) [15,16]. A review of the general area of adsorption deformation has been published by Tvardovski [17].…”
Section: Introductionmentioning
confidence: 99%
“…78,79 The osmotic free energy can be also obtained by another pathway, i.e., the integration of the adsorption isotherm with respect to the chemical potential, and this method has been applied to investigate the adsorption-induced structural transition of zeolites. [90][91][92] In contrast to the direct simulation method, free-energy analysis can represent the equilibrium behavior of the adsorption-induced structural transition successfully, but there are some limitations. One is the impossibility of reproducing the dynamics of the deformation, and the other is the difficulty of quantitatively determining the hysteretic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few examples of zeolites where flexibility has a known influence on adsorption is silicalite-1. This material was shown to possess three different crystalline structures, [25] with almost the same unit cell volumes (~0.6 % difference), between which adsorption-induced transitions were observed. [25,26] Other known flexible zeolites display this flexibility in other ways, including reversible shrinking of the framework upon solvent removal (e.g.…”
Section: Introductionmentioning
confidence: 99%